Case Report: Cardiotoxicity of capecitabine may manifest as STEMI with significant left ventricular cardiac dysfunction and recurrent supraventricular and ventricular arrhythmias: a proposal for optimal diagnosis and treatment - Szmit, Sebastian; Wojciechowska, Małgorzata; Sobera, Barbara; Szczypiorski, Krystian; Poprawa, Izabela; Gralak-Łachowska, Dagmara; Zarębiński, Maciej (Frontiers in Oncology, 2025)
Colorectal cancer is one of the most prevalent cancers globally, representing approximately 10% of all cancer cases. Due to its prevalence, an important issue is the cardiotoxicity of chemotherapy used in the course of the disease. In this article, we present the case of a patient with sigmoid cancer T3N1M0 and rectal cancer T2N0M0 who started postoperative chemotherapy according to the XELOX (CAPOX) regimen (oxaliplatin with capecitabine). A few days later, he experienced chemotherapy-related myocardial injury, which presented clinically as an ST-segment elevation myocardial infarction and was further complicated by atrial fibrillation, a severe ventricular arrhythmia, and cardiac arrest. Urgent angiography excluded significant changes in the coronary vessels, but a marked reduction in left ventricular systolic function was observed in echocardiography. Takotsubo syndrome and myocarditis were included in the differential diagnosis. Finally, a transient coronary artery spasm was deemed the most probable cause, as temporary ST-segment elevation episodes were noted on the ECG in the initial days of hospitalization. Cardiological treatment resulted in significant improvement of the clinical condition, including improvement of left ventricular systolic function and cessation of arrhythmias. Immediately after leaving the hospital, the patient received LifeVest for the prevention of sudden death and then was qualified for implantable cardioverter–defibrillator (ICD) implantation. The importance of the above adjuvant chemotherapy for the prognosis has been confirmed by the fact that after 1 year of observation, the patient experienced a cancer relapse with metastases to the lungs and peritoneum. Conclusions: This case highlights that severe cardiovascular toxicity from cancer treatment remains a significant issue, critically affecting patient prognosis. Identifying predictors of such complications is essential to enable early prevention. An alternative approach may involve the development of novel anticancer treatments with reduced cardiotoxicity.